Physicochemical properties and cell proliferation and adhesive bioactivity of collagen-hyaluronate composite gradient membrane - Li, Zhaoxuan; Song, Xue; Fan, Yan; Bao, Yuming; Hou, Hu (Frontiers in Bioengineering and Biotechnology, 2023)
Membrane materials were widely used in guided tissue regeneration (GTR) to prevent fibroblast invasion and form a confined area for preferentially growing of osteoblast. A novel collagen-hyaluronate composite gradient membrane was prepared by Tilapia (Oreochromis mossambicus) skin collagen and sodium hyaluronate for potential GTR applications and their bioactivities were investigated by cellular viability. SEM results indicated the membrane showed a dense outer and a porous inner surface for effectively guiding the growth of bone tissue. Physicochemical and biosafety experiments showed the tensile strength of membrane was 466.57±44.31 MPa and contact angle was 74.11°, and the membrane showed perfect biocompatibility and cytocompatibility as well, which met the requirements of GTR material. Cell morphology revealed that the membrane could facilitate the adherence and proliferation of fibroblast and osteoblast. The results of qRT-PCR and ELISA demonstrated that the membrane could effectively activate TGF-β/Smad pathway in fibroblast, and promote the expressions of TGF-β1, FN1 and VEGF. Remarkably, RUNX2 was stimulated in BMP2 pathway by the membrane to regulate osteoblast differentiation. In summary, the collagen-hyaluronate composite gradient membrane not only fulfills the prerequisites for use as a GTR material but also demonstrates substantial potential for practical applications in the field.